Pembangunan Web Service Data Masyarakat Menggunakan REST API dengan Access Token - Muhammad Iqbal Perkasa; Eko Budi Setiawan (Ultima Computing : Jurnal Sistem Komputer, 2018)
Data is one of the most important things in this information and information technology era that evolving now. Currently, the government still has not used the public data maximally for administrative purposes. Utilization of this big population data is the creation of a web service application system with REST API where this data will be open and accessible to those who have access. One of the institutions that use this service is the Manpower and Transmigration Service where this system can make the Dinas staff more efficient to create and register job search cards using available community data. This application is able to provide and facilitate many parties, such as data administrators to monitor data usage, registration employee in input data, and people able to register independently. Index Terms—Web service, API, Rest api, People data